Effect of an Empowerment Intervention on Antiretroviral Drug Adherence in Thai Youth - Kaihin,R. (Routledge, 2015)
A pilot study was conducted to determine effects of an empowerment intervention on antiretroviral therapy (ART) adherence among Thai youth living with HIV/AIDS. It compared two groups of 23 young persons (15–24 years) who receive ART from AIDS clinics at 2 community hospitals. One hospital's patients served as the experimental group, and the other as a control group. The experimental groups attended five sessions that empowered them to take control of their own health. The control group received standard of care. The data were analyzed using descriptive statistics and Chi-square statistics. Before the empowerment, no one from the experimental group or the control group had ART adherence ≥ 95%. After the intervention, the 82.6% of the experimental group had ≥95% adherence compared to the control group, which had 21.7% adherence (p < .0001). The empowerment intervention resulted in a significant increase in ART adherence among Thai youth.